Implementation of Field Massage to Prevent Neonatal Jaundice - Nurazizah, Dellaelvinta; Krismiyati, Murti; Fauziandari, Erma Nur (Global Health Science Group, 2024)
In 2022 Indonesia's infant mortality rate is still high, one of the causes is neonatal jaundice. Neonatal jaundice is a jaundice due to hyperbilirubinemia. Hyperbilirubinemia can be prevented by breastfeeding on demand and field massage. Field massage is the provision of stimulation in the face, chest and abdominal area which functions to increase the activity of the vagus nerve. This study aims to determine the results of the application of field massage to the prevention of neonatal jaundice. This type of research is qualitative with a case study research method using an observational approach. The data used is primary data. This research was conducted on baby Kenzo. Field massage is carried out on Baby Kenzo from birth to 6 days old, in a day it is done 2 times in the morning and evening for 15-20 minutes. The evaluation of field massage was carried out on the 6th day. after field massage there was an increase in the frequency of breastfeeding, elimination of bowel movements and urination, the baby did not experience hyperbilirubinemia and there was a weight gain of 200 grams. Field massage can improve the work of the digestive system so that it is effective in preventing neonatal jaundice.